2018
DOI: 10.1002/hep.29856
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography is useful in diagnosing biliary atresia and predicting prognosis after hepatoportoenterostomy

Abstract: LSM assessment during the workup of cholestatic infants may facilitate the diagnosis of BA. LSM post-HPE may predict complications and the need for early LT in infants with BA. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 29 publications
2
82
0
Order By: Relevance
“…We reported that the noninvasive assessment of liver fibrosis by transient elastography in infants with cholestasis may assist the diagnosis of biliary atresisa. 18 However, transient elastography is not frequently used in pediatric medicine. Hence, other noninvasive biomarkers of liver fibrosis remains needed.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that the noninvasive assessment of liver fibrosis by transient elastography in infants with cholestasis may assist the diagnosis of biliary atresisa. 18 However, transient elastography is not frequently used in pediatric medicine. Hence, other noninvasive biomarkers of liver fibrosis remains needed.…”
Section: Discussionmentioning
confidence: 99%
“…Where will the future BA innovations come from? It is a fairly safe bet that there will be an increasingly important and significant proportion from Asia . From a standing start in the early 2000s, much of the current BA research already originates from Chinese institutions .…”
Section: Discussionmentioning
confidence: 99%
“…A fascinating analysis of elastographic assessment of liver stiffness in infants who were subsequently diagnosed with BA revealed an alarming progression of disease in the first weeks of life (Fig. ) . Superimposed on the data are colored bands of ranges for normal values in older children (Fig.…”
mentioning
confidence: 96%